227k views
4 votes
What is the product ?
(4y-3)(2y^2+3y-5)

User Arun Siva
by
5.8k points

2 Answers

3 votes

Answer:

=8y^3+6y^2−29y+15

Explanation:

(4y−3)(2y^2+3y−5)

=(4y+−3)(2y^2+3y+−5)

=(4y)(2y^2)+(4y)(3y)+(4y)(−5)+(−3)(2y^2)+(−3)(3y)+(−3)(−5)

=8y^3+12y^2−20^y−6y^2−9y+15

=8y^3+6y^2−29y+15

User Nothingness
by
5.0k points
1 vote

Answer:

8y^3 + 6y^2 - 29y + 15

Explanation:

8y^3 + 12y^2 - 20y - 6y^2 - 9y + 15

then

8y^3 + 6y^2 - 29y + 15 is the product

Best regards

User Faraz Khonsari
by
5.2k points